Yoga in Pregnancy: A Preventive measure to avoid Garbha Vyapads - Suneha; Vivek; M S, Sathwik; Shiraguppi, Sunita (International Research Journal of Ayurveda & Yoga, 2021)
Simple methods like regular medical check-up, regular exercise, healthy eating can be helpful for Garbhini in maintaining good health. Apart from consanguineous intervention, social and psychological support is important too during pregnancy. At this juncture, Yoga is honored as one of the effective methods of healthcare to manage the garbhini-sutika problems. Addition of yoga asanas during gestational period simply determines the body-mind practice which encompasses the conventional substantial pose and can integrate mandatory factors, like meditation and breathing exercises. Yoga supportively helps to regulate the physiological functioning and improves psychological well-being. A positive effect upon mother and fetus may be seen if garbhini undergoes regular Yogic practices.